A novel cooler for the thermal management of solid oxide fuel cell stack. (December 2021) - Zheng, Keqing; Sun, Ya; Shen, Shuanglin; Li, Li; Wang, Shaorong
Abstract: In this work, a novel cooler for the thermal management of solid oxide fuel cell (SOFC) stack is proposed. By precisely controlling the endothermic ammonia cracking reaction in the cooler, the heat released during the operation of the fuel cell is absorbed, thereby reducing the maximum temperature difference in the SOFC stack. As a preliminary verification, a two-dimensional (2D) model of a typical SOFC unit combined with the proposed cooler is established, based on which the temperature distribution in the SOFC unit under typical SOFC operating conditions are simulated. The calculation results show that the maximum temperature difference Δ T max can be reduced to 3.9 K, when x NH3 = 0.2, u cooler = 1 m/s and U = 0.8 V. This work proves the superiority of the proposed cooler compared to traditional SOFC thermal management method using excess air.